2018
DOI: 10.18553/jmcp.2018.17337
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drug Titration and Related Health Care Resource Use and Costs

Abstract: UCB Pharma sponsored this study and reviewed the manuscript. Fishman and Kalilani are employees of UCB Pharma. Wild was an employee of UCB Pharma at the time this analysis was conducted. Song and Swallow are employees of Analysis Group, which received funding from UCB Pharma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Slow dose titration in pediatric patients was advocated to decrease side effects and to optimize treatment. 20 Consistent with previous work, a high follow-up rate was reported in this study -but the frequency of medication change was low, and average AEDs doses were lower than the recommended doses. In addition, this study reported a large percentage of patients on less than the recommended doses, which could explain most patients not having 100% response, along with a lack of significant difference between response at the start and end of follow-up.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Slow dose titration in pediatric patients was advocated to decrease side effects and to optimize treatment. 20 Consistent with previous work, a high follow-up rate was reported in this study -but the frequency of medication change was low, and average AEDs doses were lower than the recommended doses. In addition, this study reported a large percentage of patients on less than the recommended doses, which could explain most patients not having 100% response, along with a lack of significant difference between response at the start and end of follow-up.…”
Section: Resultssupporting
confidence: 92%
“…Although slow dose titration is desirable, physicians must balance this with some rapid decisions to respond to improvement on the patient's side. 19,20 Despite that side effects were assessed at each visit, adherence was not checked. Therefore, it was not possible to conclude that the presence of an adverse effect affected drug compliance or subsequent response.…”
Section: Resultsmentioning
confidence: 99%
“…However, a conservative approach was assumed in the simulation, and the January 2019 cost [53] of the most affordable retail drugs (excluding value-added tax) and package sizes formulated as capsules or tablets were used. Titration periods of perampanel and the subsequent AEDs (rounded to the closest full pack) used after brivaracetam or perampanel were modeled based on the summaries of product characteristics (SPC) and a study by Fishman et al [54]. AED dosing at the maintenance phase was based on Finnish data published by Mäkinen et al [17].…”
Section: Costsmentioning
confidence: 99%
“…The primary aim of epilepsy treatment is to minimize the number of seizures experienced by patients and to ensure that there are as few treatment-emergent adverse events (TEAEs) as possible. Sillanpää et al [15] estimated that epilepsy costs (in Euros) were €176 million in Finland in 2004, 54.5% of which included costs from registries that were indirect costs resulting from sick leave, early retirement, and premature deaths. In Sweden, indirect costs declined between 2005 and 2011 on increasing the use of AEDs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Dose titration is commonly used in most AEDs to decrease the adverse events and improve tolerability. [ 17 ] Measuring antiepileptic drug concentration level (therapeutic drug monitoring) is frequently used to optimize individual drug therapy. Monotherapy titration is titrating a single drug slowly and gradually to the desired dose.…”
Section: Introductionmentioning
confidence: 99%